The Mediating Role of Cognitive Biases and Difficulty in Emotion Regulation in the Relationship between Personality and Character with Negative Symptoms in Schizophrenia - Razmyar , Hadi; Mansouri, Ahmad; Ahi, Qasem; Bahreinian, Seyed Abdolmajid; Saied, Fahime (Health Nexus, 2025)
Negative symptoms result in a significant burden of illness and reduced quality of life in individuals with schizophrenia; therefore, the main aim of the present study was to investigate the mediating role of cognitive biases and difficulty in emotion regulation in the relationship between personality and character with negative symptoms of schizophrenia. This study was descriptive and correlational. The statistical population included all people with schizophrenia hospitalized in Razi Psychiatric Hospital in 2023-2024, of which 200 people were selected as the research sample using a convenience method. The data collection tools included the Positive and Negative Symptom Scale, Short Form of the Big Five Personality Factors Questionnaire, Short Version of the Temperament and Character Questionnaire, Cognitive Bias Assessment Scale and Short Form of Difficulties in Emotion Regulation. SPSS, and LISREL software were used for data analysis, as well as Pearson correlation method and structural equation modeling. The results showed that cognitive biases and difficulty in emotion regulation have a mediating role in the relationship between personality (neuroticism, extraversion and agreeableness) and character (self-direction, cooperation and self-transcendence) with negative symptoms of schizophrenia (CFI=1, NNFI=0.99, IFI=1, GFI=0.99, RMSEA=0.049). Individuals with schizophrenia with personality traits of neuroticism, extraversion, and character (self-direction and cooperation) experience negative symptoms due to cognitive biases and difficulty in emotion regulation. Therefore, training in emotion regulation skills and reducing cognitive biases may be an important initial component of the challenging task of treating negative symptoms of schizophrenia.